Analysis of Employee Behavior in Improving the Quality of Hajj and Umrah Services in the Industry 4.0 and Society 5.0 Era at the Banjar Regency Office of the Ministry of Religious Affairs - Maulana, Erfan; Khuzaini, Khuzai; Shaddiq, Syahrial; Junaidy, Junaidy; Irpan, M.; Surya, Adhi; Saputra, Riki Welli; Sulastini, Sulastini; Noor, Meitria Syahadatina; Auliah, Nurul (Hut Publication Business and Management, 2024)
The public service provided by the Office of the Ministry of Religious Affairs (Kemenag) in Banjar Regency focuses on facilitating Hajj and Umrah services. With the continuous increase in the number of prospective Hajj pilgrims in Banjar Regency, it is essential to provide quality services. Employees need to exhibit behavioral competencies to address challenges in the current era, encompassing three aspects: employee behavior in communication and social skills, adaptability and task completion, and technological skills. This research aims to analyze employee behavior in enhancing the quality of Hajj and Umrah services in the era of Industry 4.0 and Society 5.0 at the Ministry of Religious Affairs office in Banjar Regency. This qualitative research adopts a cross- sectional approach conducted over one month. Twenty respondents were selected using convenience sampling. Data were collected, transcribed, translated, and then subjected to directed content analysis to identify main themes. It is observed that employees' behavior in communication and social skills, as well as adaptability and task completion aspects, have been implemented effectively. However, the technological skills aspect is deemed suboptimal. There is a need for improvement in technological skills and a shift in mindset among employees to address the challenges of Industry 4.0 and Society 5.0.